Understanding of TEMPO-electrocatalyzed acceptorless dehydrogenation of tetrahydroquinoline by in situ extractive electrospray ionization mass spectrometry. Issue 23 (23rd February 2021) - Li, Weixiang; Sun, Jianghui; Wang, Yan; Qiao, Jinping; He, Lixin; Ouyang, Jin; Na, Na
Abstract : The TEMPO-electrocatalyzed acceptorless dehydrogenation of tetrahydroquinoline was investigated by coupling an electrocatalytic system to in situ extraction electrospray ionization mass spectrometry. Abstract : The TEMPO-electrocatalyzed acceptorless dehydrogenation of tetrahydroquinoline, a transformation in green synthesis and hydrogen storage, has been investigated by coupling of an electrocatalytic system with in situ extraction electrospray ionization mass spectrometry. Dynamic changes in important species and intermediates were monitored, which evoked an updated AD understanding.